Composition characteristics of siloxane derived waste lubricating oil and its effect on low-rank coal flotation. (1st December 2021) - Yang, Zhe; Liao, Yinfei; An, Maoyan; Ren, Hourui; Hao, Xiaodong; Song, Xingwei; Liu, Zechen
Graphical abstract: Highlights: A thorough investigation on the waste siloxane-based lubricant chemical composition. Extend disposal application of waste siloxane motor oil as flotation collector. High quality and clean products produced in siloxane-coal flotation process. Abstract: Waste motor oil/lubricating oil (WMO) is a hazardous and important resource. The waste siloxane-based motor oil/lubricating oil (WSMO) has a special composition based on siloxane. The WSMO has a large and increasing production worldwide. In this paper, the feasibility of WSMO as a collector for low-rank coal (LRC) flotation was discussed with a comparison to diesel oil (DO). The gas chromatography-mass spectrometry (GC/MS) and thermal gravimetric analysis (TGA) were used to analyze the chemical composition of WSMO. The flotation experiment was conducted to investigate the collectivity and selectivity of WSMO as an LRC collector. The interaction between WSMO and LRC was systematically analyzed using X-ray photoelectron spectroscopy (XPS), contact angle, zeta potential, and induction time measurements. The results indicated that WSMO majorly contained dimethylsiloxane and cyclodimethysiloxane with various chain lengths. High concentrates yield and low ash content was obtained in the flotation using WSMO. The adsorption of WSMO can mask the oxygen-containing groups (OCGs) on the LRC surface, leading to an increase of C content and a decrease in O content. This was beneficial to improve the hydrophobicity of the LRC surface so that the water-coal contact angle increased from 35.6° to 57.85° after WSMO treatment. Moreover, a significant increase in zeta potential was observed in the pH range of 4 to 10. LRC particles pretreated with WSMO were more easily adhere to the bubble surface in a short induction time of 40 ms. It was demonstrated that WSMO was an effective collector to promote LRC flotation.